2012
DOI: 10.1161/circulationaha.111.086983
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Longitudinal Function Predicts Life-Threatening Ventricular Arrhythmia and Death in Adults With Repaired Tetralogy of Fallot

Abstract: Background-Suddenwere related to the combined end point. On bivariable analysis, mitral annular plane systolic excursion and LV global longitudinal 2-dimensional strain were related to outcome independently of QRS duration (Pϭ0.002 and Pϭ0.01, respectively). In addition, a combination of echocardiographic variables, including right atrial area, right ventricular fractional area change, and LV global longitudinal 2-dimensional strain or mitral annular plane systolic excursion, was also found to be significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
129
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 243 publications
(141 citation statements)
references
References 47 publications
(52 reference statements)
8
129
0
4
Order By: Relevance
“…Furthermore, several ECG parameters, including QRS duration, change rate of QRS duration, QT/JT duration and dispersion, heart rate variability, and fragmented QRS, have been recognized as risk factors for life threatening ventricular arrhythmias and SCD (1,4,6,7,12,13). Residual cardiac lesions or hemodynamic abnormalities are associated with late SCD, including elevated RV pressure due to RVOT obstruction or pulmonary artery stenosis, right ventricular volume load, right ventricular dysfunction, left ventricular longitudinal dysfunction, and left ventricular diastolic dysfunction (5,14). Despite these studies, no single risk factor has yet been identified to predict VT and SCD in patients who have undergone TOF repair.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, several ECG parameters, including QRS duration, change rate of QRS duration, QT/JT duration and dispersion, heart rate variability, and fragmented QRS, have been recognized as risk factors for life threatening ventricular arrhythmias and SCD (1,4,6,7,12,13). Residual cardiac lesions or hemodynamic abnormalities are associated with late SCD, including elevated RV pressure due to RVOT obstruction or pulmonary artery stenosis, right ventricular volume load, right ventricular dysfunction, left ventricular longitudinal dysfunction, and left ventricular diastolic dysfunction (5,14). Despite these studies, no single risk factor has yet been identified to predict VT and SCD in patients who have undergone TOF repair.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of post-repaired patients survive and reach adulthood, although some patients are at risk of several life-threatening complications, such as arrhythmia and sudden cardiac death (SCD) (1,2). Numerous reports have identified risk factors for ventricular tachyarrhythmia, including QRS duration, change rate of QRS duration, QTc duration, delay in corrective surgery, number of previous cardiac surgery, presence of ventriculotomy, trans-annular patch (TAP) repair, and left ventricular diastolic dysfunction (3)(4)(5)(6)(7). Those …”
Section: Introductionmentioning
confidence: 99%
“…In a study of repaired adult tetralogy, left ventricular longitudinal dysfunction was associated with greater risk of sudden cardiac death or life-threatening arrhythmias. 44 The authors conclude that, in combination with echocardiographic right heart variables, these measures provided important outcome information for estimating prognosis.…”
Section: Tetralogy Of Fallotmentioning
confidence: 96%
“…• Transannular patch 18 • Severe pulmonary regurgitation 18 • Right ventricular hypertrophy 20 • Right ventricular dilation 22 • Right ventricular systolic dysfunction 20 • Left ventricular systolic dysfunction 82 • QRS duration ≥ 180 ms 18,22 Transposition of the Great Arteries…”
Section: Tetralogy Of Fallotmentioning
confidence: 99%